2006
DOI: 10.1176/ps.2006.57.8.1185
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Providers in Mental Health Services Offered to American-Indian Youths

Abstract: The results demonstrate that professional, informal, and traditional providers play a pivotal role in providing treatment services offered to American-Indian youths and that these providers were more likely to identify a youth's problems and to offer and refer services when the provider knew more about community resources for the youth and about the youth's personal and environmental problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Friends might exert negative peer pressure by encouraging selfdestructive behaviors, discouraging other help seeking, or responding in a stigmatizing fashion. Conversely, friends and family themselves can provide services similar to those of mental health professionals by listening, giving advice, and providing information about available resources (Stiffman et al, 2006). Pescosolido, Wright, Alegria, and Vera (1998) found that large social support networks decreased the likelihood of a person obtaining professional help for mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Friends might exert negative peer pressure by encouraging selfdestructive behaviors, discouraging other help seeking, or responding in a stigmatizing fashion. Conversely, friends and family themselves can provide services similar to those of mental health professionals by listening, giving advice, and providing information about available resources (Stiffman et al, 2006). Pescosolido, Wright, Alegria, and Vera (1998) found that large social support networks decreased the likelihood of a person obtaining professional help for mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…We expected that an examination of help-seeking would result in a greater number of contacts compared to studies that examined only services received (e.g., Verhulst and Van der Ende 1997;Zwaanswijk et al 2007). In addition to the number of contacts, we analyzed parents' help-seeking efforts over time rather than focusing on a single end-point of being referred and/or receiving services (e.g., Stiffman et al 2006).…”
Section: The Current Studymentioning
confidence: 99%
“…The role of religious leaders in community mental health can be considered in terms of the Gateway Provider Model (GPM; Stiffman et al 2004). The GPM emphasises the role of key community individuals who can facilitate the identification of mental health issues and provide a gateway to mental health services (Stiffman et al 2006, Ellis et al 2010. The clergy are an important example of 'gateway providers' because they have a salient influence over their institutions and shape the physical and social environments for community health (Bopp et al 2013).…”
Section: Introductionmentioning
confidence: 99%